2022
DOI: 10.1007/s11547-022-01504-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum Krebs von den Lungen-6 and chest CT as potential prognostic factors in severe acute respiratory syndrome SARS-CoV-2: a preliminary experience

Abstract: Purpose To correlate in COVID-19 pneumonia CT-based semi-quantitative score of pulmonary involvement with high serum levels of KL-6, a biomarker of disease severity. Methods Between March 28 to May 21, 2020, 196 patients with strong suspicion of SARS-CoV-2 were evaluated with RT-PCR for SARS-CoV-2, chest CT scan and blood test, including KL-6 serum protein, in our Emergency Unit. The final population included only patients who underwent blood sampling for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…These articles were re-evaluated based on full-text contents, resulting in exclusion of 8 articles. Finally, 15 studies met the inclusion criteria and were included in our meta-analysis ( Figure 1 ) [ 5 , 8 , 12 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All selected studies were published between 2020 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These articles were re-evaluated based on full-text contents, resulting in exclusion of 8 articles. Finally, 15 studies met the inclusion criteria and were included in our meta-analysis ( Figure 1 ) [ 5 , 8 , 12 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. All selected studies were published between 2020 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies in our meta-analysis compared KL-6 concentrations in COVID-19 cases and healthy subjects [ 12 , 20 , 21 , 22 , 23 , 27 ]. Results showed that KL-6 is significantly higher in COVID-19 than in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research aiming to investigate the relationship between KL-6 and chest CT scan documented a significant correlation between KL-6 and the extension of parenchymal lesions using a CT semiquantitative score. In particular, the authors found a higher frequency of crazy paving patterns and consolidations involving the right upper and middle lobe in COVID-19 patients with KL-6 > 400 U/mL [ 32 ].…”
Section: Discussionmentioning
confidence: 99%